Detection of fracture in ceramic cutting tools from workpiece proﬁle signature using image processing and fast Fourier transform - Lee, W.K.; Ratnam, M.M.; Ahmad, Z.A. (Elsevier Ltd, 2016)
A non-contact vision-based method to detect the occurrence of fracture in ceramic cutting tool inserts using the workpiece proﬁle signature is proposed. Machining experiments were carried out to turn stain-less steel using ceramic cutting tool inserts. The images of the workpiece proﬁle were captured after each turning pass using a high-resolution DSLR camera. The edge proﬁles of the workpiece were extracted to sub-pixel accuracy using the invariant moment method. The extracted proﬁles were transformed from the spatial domain to the frequency domain using Fast Fourier Transform (FFT). From the Fourier spec-trum the amplitude of the fundamental feed frequency was observed to increase steadily with the cutting duration during gradual wear of the tool edge. However, signiﬁcant ﬂuctuations in the amplitude of the fundamental feed frequency were observed after the onset of chipping and fracture due to the contin-uous deterioration of the cutting edge. This was caused by the irregular peak-to-valley heights in the workpiece surface proﬁle resulting from the fractured tool at the end of the cutting time of 84.8 s.